The Impact of Artificial Intelligence on the Digital Economy: Advances and Challenges - A Systematic Literature Review - Matamoros-Echeverria, Karen Lissette; Sanchez-Leon, Edwin Roberto; Aristega-Zuñiga, Antonio Alejandro; Cárdenas-Rodríguez, Mario Manuel; Peralta-Gamboa, Dennis Alfredo (Journal of Posthumanism, 2025)
The digital economy has undergone a significant transformation in recent years due to the impact of artificial intelligence (AI). This study presents a systematic literature review to analyze AI’s advances and challenges in the digital economy. A search was conducted in databases such as Web of Science and Scopus, selecting 36 relevant studies published between 2021 and 2025. The findings indicate that AI has optimized process automation, improved operational efficiency, and strengthened transparency in the digital economy. However, challenges related to regulation, data privacy, and inequality in technology adoption persist. This study provides a comprehensive overview of how AI is reshaping the digital economy and highlights the need for regulatory and technological development strategies to ensure ethical and equitable implementation.